Android Learning Media Development to Improve Spatial Ability - Syariful Fahmi; Widayati Widayati; Soffi Widyanesti Priwantoro (Phenomenon : Jurnal Pendidikan MIPA, 2022)
The research aims to produce an interactive learning media. This research is included in the type of development research, using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The software used in this interactive learning media is Adobe Flash CS 6 and Unity as the main software. The research was carried out at SMP Muhammadiyah 7 Yogyakarta with the subject of 31 students of class VIII C in the 2020/2021 academic year. The research data was obtained from the results of material validation questionnaires by material experts, media validation questionnaires by media experts, and student response questionnaires by students. The feasibility of this interactive learning media is obtained from the process of quantitative and qualitative data analysis. The product of this development research is in the form of mathematics learning software for class VIII that can be downloaded and operated on android-based mobile phones. Based on the results by material experts, media experts, and students , this product obtained an average feasibility score of 77; 118.5; and 78.87 with very good, very good, and good qualitative categories. Thus, the interactive learning media product that has been successfully developed is suitable for use in the mathematics learning process